Countdown to eternity a study of dispensationalism - Mackay, Harold G.; Emmaus Bible School (Oak Park, IL Emmaus Bible School, 1973)
Includes bibliographical references.
Original text material by Harold MacKay. Developed as a correspondence course by Emmaus Correspondence School.
Keywords: Dispensationalism -- study and teaching